Muslim Renaissance - Louay M. Safi (International Institute of Islamic Thought, 2003)
The last three decades have brought profound changes to how we look at the funadmental notions that define the modern world, such as culture, ideology, religion, reform, and progress. A drastic shift from a bipolar world defined by the rivalry betweeen the liberal West and the communist bloc in the 1980s, to a globalization intent upon breaking both market and cultural barriers in the 1990s, to a new form of polarization driven by religious and cultural exclusivism at the turn of the twenty-first century. Not only has communism succumbed and disappeared as a credible sociopolitical force, but liberalism itself is in retreat even in the United States, the most liberal society of all, giving way to a new tide of conservatism. Evidently, the tide of conservatism seeking to replace both progressive and revolutionary movements does not bring new hopes of a better future; rather, it seems to be bent on reclaiming old postures of selfrighteousness and ethnicity that fueled hatred, international hostility, and wars. Secularist idedologies are giving rise to religious ideologies, as can be seen clearly in almost every culture, whether in the United States, India, or Turkey. In Muslim societies, religious conservatism has cloaked the Islamic reform movement’s forward vision and threatens to roll back its achievements. The reform movement also has been suppressed by the overbearing political regimes ruling the Muslim world. Many people question whether an Islamic renaissance – or a renaissance based on Islamic values – is even posible and, if so, how does it relate to rising conservative and declining modernist ideologies? ...